Resilience in education policy: Insights from Indonesia’s school reopening amid COVID-19 - Afrizal Fajri; Sajida Sajida (Privietlab, 2026)
The COVID-19 pandemic has really left an impacted education, stimulating policymakers to introduce emergency remote learning. However, transitioning to online education has exposed huge problems in Indonesia, particularly inequalities in digital access, insufficient learning support, and mounting household costs. Finally, with many public outcries for schools to be reopened, the phased reopening policy was implemented through the SKB 4 Menteri decree. This study is hence concerned with an evaluation of the implementation and effect of school reopening policies that were put in place in Indonesia during the pandemic. The logical framework approach is used to assess inputs, processes, outputs, outcomes, and impacts. The conclusion is that the reopening of schools addresses the learning loss incurred by the students; however, these K-12 institutions do not have sufficient health infrastructure and there are poor enforcement protocols that altogether made these schools hotspot areas for the emergence of COVID clusters. However, decisions made at the policy level were reactive rather than evidence-based, portraying a gap in crisis preparedness and risk mitigation. The need to make adaptive education policies based on the lessons learned as described in this experience should be emphasized to realize the balance of learning continuity with public health priorities, strong engagement needed in terms of stakeholders, and decision-making that is based on data. The future needs of educational resilience will require strengthened digital infrastructures, hybrid learning models, and crisis-responsive governance in education.